2013
DOI: 10.1111/jace.12610
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor‐Enhanced Diffusion in Alumina

Abstract: Experimental results indicate effective faster diffusion of oxygen in polycrystalline alumina when exposed to water vapor at high temperatures. a-Al 2 O 3 containing Ni metal particles was exposed to dry air or humid environments at 1300°C for up to 20 h. Oxidation of Ni in a-Al 2 O 3 to form NiAl 2 O 4 was used to determine oxygen diffusion depth from the surface. The apparent kinetic rate constant for oxygen diffusion in the presence of water vapor was 79% higher compared with that in a dry atmosphere at 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Similarly, Maris-Sida et al [4] postulated that water vapour could be responsible for the enhanced diffusion of divalent cation (e.g., Ni 2+ ) across the TGO scale by altering the defect structure of the scale through proton incorporation. In addition, Angle et al [13] showed that water vapor could enhance the inward diffusion of oxygen into α-Al 2 O 3 scale. They suggested that proton incorporation could effectively convert O 2− species to OH − , in which their smaller size, increased polarity and the decreased charge state allow us to penetrate more deeply into the ceramic scale along the grain boundaries.…”
Section: Effect Of Water Vapour Effect Bond Coatmentioning
confidence: 99%
“…Similarly, Maris-Sida et al [4] postulated that water vapour could be responsible for the enhanced diffusion of divalent cation (e.g., Ni 2+ ) across the TGO scale by altering the defect structure of the scale through proton incorporation. In addition, Angle et al [13] showed that water vapor could enhance the inward diffusion of oxygen into α-Al 2 O 3 scale. They suggested that proton incorporation could effectively convert O 2− species to OH − , in which their smaller size, increased polarity and the decreased charge state allow us to penetrate more deeply into the ceramic scale along the grain boundaries.…”
Section: Effect Of Water Vapour Effect Bond Coatmentioning
confidence: 99%
“…Interestingly, recent work has also pointed to the possible role of water in the RE effect. 9,10 In an effort to isolate the effect of the RE on GB transport, and to achieve stricter compositional control, several groups have carried out model studies on polycrystalline alumina. For example, Matsudaira and co-workers 11,12 have studied the permeability of oxygen in doped alumina wafers in the temperature range 1500°C-1700°C.…”
Section: Introductionmentioning
confidence: 99%
“…Unambiguous interpretation of data is also made more difficult by the associated effects of REs on scale microstructure and adhesion. Interestingly, recent work has also pointed to the possible role of water in the RE effect 9,10 . In an effort to isolate the effect of the RE on GB transport, and to achieve stricter compositional control, several groups have carried out model studies on polycrystalline alumina.…”
Section: Introductionmentioning
confidence: 99%
“…We will use an approach adopted previously to probe the effect of yttrium doping, namely the utilization of Ni marker particles dispersed in a dense alumina processed from high‐purity powders . Angle et al . have also exploited this technique to study the effect of water vapor on oxygen grain‐boundary transport in alumina.…”
Section: Introductionmentioning
confidence: 99%
“…We will use an approach adopted previously to probe the effect of yttrium doping, namely the utilization of Ni marker particles dispersed in a dense alumina processed from high-purity powders. 33,42 Angle et al 43 have also exploited this technique to study the effect of water vapor on oxygen grain-boundary transport in alumina. During high-temperature annealing of the samples in an oxidizing atmosphere, the Ni particles react with the oxygen to form NiAl 2 O 4 spinel, hence delineating the oxidation front.…”
Section: Introductionmentioning
confidence: 99%